Da’i (Muslim Preachers) Idols, Fatwas, and Political Constellations: Empirical Study of Millennial Generation Perspective - Fahrudin Fahrudin; Mohammad Rindu Fajar Islamy (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to track the phenomenon of da'i (Muslim Preachers) idols among the millennial generation and its impact on the dynamics of accepting contemporary fatwas and the constellation of leader elections in Indonesia. The da'wah transformation from traditional methods to digital media is increasingly adding to the dynamics of changing the youth's perspective in responding to life's problems, such as religious fatwas and political constellations. This study uses mixed methods research. The data collection technique used google Forms by taking 95 respondents, and semi-structured interviews with five informants using random sampling with the criteria enjoy listening to digital da'wah. Data analysis applies the theory of Miles and Huberman with the following steps: data collection, data display, data reduction, and conclusion. The research results show several essential points, including; 1) There is an urgency in the need for da'wah studies in filling the pressure of problems faced by the millennial generation, 2) Communication style and material substance are more important than the intellectuality of a preacher, 3) In the context of certain fatwas, the Indonesian Ulema Council (MUI) is preferred to be used as a reference from their da'i idol, 4) In the context of choosing a leader, they prefer individual ijtihad to a public figure or institutional ijtihad, 5) Digital da'wah contributes significantly to character strengthening, 6) Da'wah themes vary according to the needs of listeners, and 7) characteristics of da'i idol including polite, wise, humble, broad-minded, moderate, good communication, akhlakul karimah